PENILAIAN KUALITAS HIDUP PADA PASIEN TUMOR OTAK - Sheila Agustini*, Tiara Aninditha*, Lyna Soeridewi*, Teguh AS Ranakusuma* (Neurona Majalah Kedokteran Neuro Sains, 2011)
INTRODUCTION BRAIN TUMORS COMPRISE ONLY 14 OF ALL CANCERS NEVERTHELESS THE HIGH FATALITY RATES AND THE TRAUMATIC EXPERIENCE THAT PATIENTS AND CAREGIVERS OFTEN ENCOUNTER DRAWS SPECIFIC ATTENTION BRAIN TUMORS ARE DISTINCT BECAUSE IT IS OFTEN ACCOMPANIED BY PROGRESSIVE COGNITIVE DYSFUNCTION AND FUNCTIONAL DECLINE THAT CAUSE SIGNIFICANT BURDEN BOTH FOR THE PATIENTS AND THE CAREGIVERS AVAILABLE THERAPIES RARELY BECOME A CURE FOR THE DISEASE HENCE CLINICIANS SHOULD ALSO FOCUS ON ACHIEVING THE QUALITY OF LIFE QOL